Penerapan 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) Pada Area Kerja Sebagai Upaya Peningkatan Produktivitas Kerja (Studi Kasus Di CV Widjaya Presisi) - Muhammad Reza; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2019)
CV Widjaya Presisi is a small and medium industry engaged in industrial services with its main products being automotive / electronic special tools, dies, jig fixture, stamping, and fabrication. The findings of the problem in the work area are remnants of material that is not removed so that the working space is narrow and no management and supervisors regulate the work environment and work safety. This study aims to implement the 5S design to existing conditions. This study uses a qualitative method, namely the 5S method. The seiri stage is designed by sorting out the equipment that is important, very important, not important and very insignificant. Seiton stage is designed by arranging goods according to the type of goods. The seiso stage is designed by making cleaning areas. The seiketsu stage is designed by providing visual control in the form of labeling, marking, and area boards. The Shitsuke stage is designed by doing activities by making 5S as a rule into the company's standard activity system. After repairs, working time can be optimized from 840 minutes to 810 minutes or a decrease of 4% from work time. The average work productivity in March 2019 and April 2019 amounted to 99.5% where in February 2019 the productivity level was only 57% and experienced a significant increase in March 2019 by 99% and April 2019 by 100%.